Equine Stereotaxtic Population Average Brain Atlas With Neuroanatomic Correlation - Johnson, Philippa J.; Janvier, Valentin; Luh, Wen-Ming; FitzMaurice, Marnie; Southard, Teresa; Barry, Erica F. (Frontiers in Neuroanatomy, 2019)
There is growing interest in the horse for behavioral, neuroanatomic and neuroscientific research due to its large and complex brain, cognitive abilities and long lifespan making it neurologically interesting and a potential large animal model for several neuropsychological diseases. Magnetic resonance imaging (MRI) is a powerful neuroscientific research tool that can be performed in vivo, with adapted equine facilities, or ex-vivo in the research setting. The brain atlas is a fundamental resource for neuroimaging research, and have been created for a multitude animal models, however, none currently exist for the equine brain. In this study, we document the creation of a high-resolution stereotaxic population average brain atlas of the equine. The atlas was generated from nine unfixed equine cadaver brains imaged within 4 h of euthanasia in a 3-tesla MRI. The atlas was generated using linear and non-linear registration methods and quality assessed using signal and contrast to noise calculations. Tissue segmentation maps (TSMs) for white matter (WM), gray matter (GM) and cerebrospinal fluid (CSF), were generated and manually segmented anatomic priors created for multiple subcortical brain structures. The resulting atlas was validated and correlated to gross anatomical specimens and is made freely available at as an online resource for researchers (https://doi.org/10.7298/cyrs-7b51.2). The mean volume metrics for the whole brain, GM and WM for the included subjects were documented and the effect of age and laterality assessed. Alterations in brain volume in relation to age were identified, though these variables were not found to be significantly correlated. All subjects had higher whole brain, GM and WM volumes on the right side, consistent with the well documented right forebrain dominance of horses. This atlas provides an important tool for automated processing in equine and translational neuroimaging research.